Dictionary of toxicology - Hodgson, Ernest 1932-; Roe, R. Michael; Mailman, Richard B.; Chambers, Janice E. (Academic Press, an imprint of Elsevier, 2014)
Dictionary of Toxicology, 3rd Edition presents a compendium of definitions of all current toxicological terminology. This authoritative reference illustrates and describes words, concepts, acronyms and symbols for both the toxicological theory and applied risk assessment, as well as providing guidance on the correct selection of problematic, similar and frequently-misused terms. Written by one of the world's foremost experts in toxicology, and with each entry peer reviewed, Dictionary of Toxicology, 3rd Edition is an essential reference for all scientific, medical and legal professionals wh